The MCU complex in cell death. (January 2018) - Penna, Elisa; Espino, Javier; De Stefani, Diego; Rizzuto, Rosario
Graphical abstract: Abstract: During the 60s, the notion that positively charged Ca 2+ ions are rapidly accumulated in energized mitochondria has been first established. In the following decades, mitochondrial Ca 2+ homeostasis was shown to control cell metabolism, cell survival and other cell-specific functions through different mechanism. However, the molecular identity of the molecules controlling this process remained a mystery until just few years ago, when both mitochondrial Ca 2+ uptake and release systems were genetically dissected. This finally opened the possibility to develop genetic model to directly test the contribution of mitochondrial Ca 2+ homeostasis to cellular functions. Although the picture is still far from being clear, we here summarize and critically evaluate the current knowledge on how mitochondrial Ca 2+ handling controls cell death.